Origin of low salinity, high volume produced waters in the Wolfcamp Shale (Permian), Delaware Basin, USA. (November 2020) - Nicot, Jean-Philippe; Darvari, Roxana; Eichhubl, Peter; Scanlon, Bridget R.; Elliott, Brent A.; Bryndzia, L. Taras; Gale, Julia F.W.; Fall, András
Abstract: The Wolfcamp Shale within the Delaware Basin of West Texas and southeastern New Mexico is one of the largest unconventional oil reservoirs globally and also produces high volumes of relatively low salinity water. In contrast, the overlying Bone Spring Formation and, particularly, the shallower Delaware Mountain Group contain very saline brines. The objective of the study was to assess source and nature of waters produced from the Wolfcamp and to frame them in the larger geological and hydrogeological evolution of the Basin. A total of ~150 produced water samples were analyzed for major and trace element chemistry and isotope data and were complemented by public domain and confidential information. The formation shows a striking total dissolved solids (TDS) distribution with low TDS water samples (<25 g/L) restricted to the basin center that increases up to 100–140 g/L towards the basin margins. Water isotopes (heavy δ 18 O +5–+8‰ and δ 2 H -25–-10‰ VSMOW) and low Cl/Br mass ratios (100–200) support the hypothesis that low-TDS waters result from water released during smectite-to-illite conversion. Chemical and isotopic data preclude a meteoric water source and mixing hydraulic fracturing water. Anomalously high Water to Oil Ratios (WORs) in the Wolfcamp Shale (~4) are associated with higher clay content in the target horizon and with low-TDS produced water. These associations are considered causative with the high water cut and low salinity being intrinsically geologic and attributed to the thick (>2 km) mudstone package of Pennsylvanian to lower Permian age, combined with the effects of the Laramide uplift and Neogene tilting of the entire Basin. Highlights: TDS of Wolfcamp formation waters are as low as <20 g/L with a maximum of 140 g/L. They represent evolved evaporative brines migrated down from thick evaporite deposits. Some Wolfcamp oil and gas wells produce an anomalously high volume of low TDS water. Low TDS wells are located in the Basin center with increasing TDS to the margins. Low TDS water results from clay diagenesis coupled with unfavorable flow conditions.